Developing a LOTS and HOTS-Based Reading Comprehension Instrument for Lower Secondary Students - Ima Chusnul Chotimah; Utami Widiati; Nunung Suryati; Mirjam Anugerahwati (Journal of Educational Studies, 2026)
To assess students’ reading comprehension, both low-level and high-level thinking tests are needed. However, the majority of lower secondary school test emphasize memorization of facts rather than offering enough information about critical thinking. This study offers a novel approach by developing a balanced reading comprehension test integrating both lower-order thinking skills (LOTS) and higher-order thinking skills (HOTS) within Barrett’s Taxonomy framework. The instrument was designed with an equal proportion LOTS and HOTS items. Employing Mardapi’s Research and Development (R&D) model, the instrument was administered to 39 lower secondary students through pre- and post-test trials. The result of item analysis revealed validity for both pre-test and post-test instruments, with 27 of 30 items retained and 3 items excluded for invalidity. Reliability levels were very high (? = 0.888 for the pre-test and ? = 0.867 for the post-test). Item difficulty analysis showed that, in the pre-test, 43.33% of items were moderate, 30% difficult, and 26.67% easy; while in the post-test, 46.67% were moderate, 43.33% difficult, and 10% easy. Item discrimination analysis indicated that 56.67% of pre-test items were excellent, 26.67% were good, 6.67% mediocre, and 10% poor; whereas in the post-test, 66.67% were excellent, 13.33% good, 6.67% mediocre, and 13.33% poor. These results show the instrument’s robus psychometric qualities and its effectiveness in differentiating students’ comprehension. Theoretically, this study contributes a validated model for integrating Barrett’s taxonomy with balanced LOTS–HOTS assessment, while practically offering teachers and researchers a tool for aligning reading assessment with students’ cognitive skill development in EFL contexts.